PENGARUH EDUKASI MENGGUNAKAN LEAFLET, AUDIO VISUAL, LEAFLET DAN AUDIO VISUALTERHADAP PENGETAHUAN, SIKAP DAN PERILAKU ORANGTUA DALAM PENCEGAHAN DIARE DI PUSKESMAS RAWAT INAP MANIS JAYA TANGERANG - Rianti, Rianti; Apriliawati, Anita; Sulaiman, Suhendar (Universitas Islam Negeri Alauddin Makassar, 2020)
Diarrhea in infants and toddlers (under five years) can be very dangerous because it can cause death.The death is caused by lack of fluid that comes out with a lot of feces. The purpose of this study is to determine the influence of education using leaflets, audiovisuals, leaflets and audiovisuals on parental behavior in preventing diarrhea in toddlers (under five years old). This study is using Quasi-Experimental design with a Pretest-Posttest Group Design approach. The sample in this study is 27 samples. The test results found there are differences on parent’s knowledge, attitudes and behavior before and after health education was given using Leaflets, Audiovisuals, Leaflets and Audiovisuals with p value <0.005. It found the difference on parent’s knowledge, attitude and behavior before and after given the health education using leaflet with each p value< 0,001, 0,010, 0,019. found the difference on parent’s knowledge, attitude and behavior before and after given the health education using audiovisual with each p value< 0,001, 0,001. 0,001. It found the difference on parent’s knowledge, attitude and behavior before and after given the health education using leaflet and audiovisual with p value< 0,001, 0.012, 0,001). The hope is for educators to improve health promotion, especially prevention of diarrhea by playing diarrhea prevention videos, so that the dissemination of this information is broader and useful for all patients, not only diarrhea patients. Keyword : Toddler, Leaflets, Audiovisual Leaflets And Audivisual, Knowledge, Attitudes, Mother's Behavior